DEVELOPMENT OF RAB INFORMATION SYSTEM VS WEBSITE-BASED REALIZATION CASE STUDY ON PT. NUSA RAYA CIPTA Tbk SEMARANG - Junadi, Bambang; Fitriani, Yuni; Utami, Sri; Widyastuti, Handini (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Project financial reports are documents used to track and present information about expenditures, and project financial performance. This report is usually prepared or created periodically (for example, every two weeks or every month) to help project management monitor the costs incurred. The project financial report must be in accordance with the Cost Budget Plan (RAB). The problem is that making the project financial report will be hampered if the costs to be reported are not listed on the RAB, the RAB must be revised. Every cost that will be included or reported in the project financial report must be cross-checked with the RAB first. The solution to the problem is to build a web-based application. The methodology used in making this application is the Waterfall method. If this application is implemented directly in the organization, it can be a solution in increasing the effectiveness and efficiency of the project report creation process